Collaborative Online Annotation: Pedagogy, Assessment and Platform Comparisons - Porter, Gavin W. (Frontiers in Education, 2022)
Annotating a text while reading is commonplace and essentially as old as printed text itself. Collaborative online annotation platforms are enabling this process in new ways, turning reading from a solitary into a collective activity. The platforms provide a critical discussion forum for students and instructors that is directly content-linked, and can increase uptake of assigned reading. However, the student viewpoint regarding collaborative online annotation platforms remains largely unexplored, as do comparisons between annotation and traditional reading assessment methods, and comparisons between the two leading platforms (hypothes.is versus Perusall) for annotation by the same student population. The results in this study indicate that collaborative online annotation is largely preferred by students over a traditional reading assessment approach, that students regularly exceed annotation requirements indicated by an instructor, and that overall annotation quality increased as the students gained experience with the platforms. The data analysis in this study can serve as a practical exemplar for measurement of student annotation output, where baselines have yet to be established. These findings link the established research areas of peer learning, formative assessment, and asynchronous learning, with an emerging educational technology.